2018
DOI: 10.1038/s41598-018-27015-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Synthesis of Core/shell Structure Au@Cu2S Nanocrystals as Contrast-enhanced for Bioimaging Detection

Abstract: In this paper, we reported Au@Cu2S nanocrystals in the aqueous phase with a core/shell structure and dBSA encapsulation. The dBSA-Au@Cu2S crystals formed with an average size of approximately 9 nm. There was a strong absorption in the near-infrared (NIR) field located at 1348 nm, and they exhibited low toxicity in the in vitro tests. Furthermore, we demonstrated that dBSA-Au@Cu2S could be used for optical coherence tomography (OCT). The in vivo experimental results show that the OCT signal increased as the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Nanocrystals of Cu 2 S, an important p-type semiconductor, have been investigated because of their substantial advantages, which include strong absorption, high photostability, and low toxicity. [62][63][64][65][66][67] They have strong potential in a wide range of applications, including solar cells, photocatalysts, thermoelectric materials, and highcapacity anode materials for lithium secondary batteries. [68][69][70][71][72] Cu@Cu 2 S hybrid nanostructures can be effectively synthesized by exposing preformed Cu nanocrystals to sulfur compounds in various oxidation states to transform them into sulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocrystals of Cu 2 S, an important p-type semiconductor, have been investigated because of their substantial advantages, which include strong absorption, high photostability, and low toxicity. [62][63][64][65][66][67] They have strong potential in a wide range of applications, including solar cells, photocatalysts, thermoelectric materials, and highcapacity anode materials for lithium secondary batteries. [68][69][70][71][72] Cu@Cu 2 S hybrid nanostructures can be effectively synthesized by exposing preformed Cu nanocrystals to sulfur compounds in various oxidation states to transform them into sulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Another report revealed that Au@Cu 2– x S was biocompatible and guaranteed biosafety at a concentration of 128 μg/mL, with MC3T3-E1 cell viability exceeding 95% . Liu et al also reported that MCF-7 cells exposed to Au@Cu 2 S nanocrystals at concentrations of 720 and 45 ppm had a viability of approximately 20 and 70%, respectively, after 24 h. The enhanced surface area and the inhibition of the assembly of AuCu and Cu 2 –S in the composite material are significant factors for heightening cytotoxic effects . Thus, not only the concentration but also the method of preparation of the AuCu–Cu 2 S nanocomposite contributes to their cytotoxic effects in vivo and in vitro.…”
Section: Cytotoxicity Study Of Aucu–cu2smentioning
confidence: 99%
“…It is ubiquitous in complex structures to combine two or more different metal materials to improve their physical, optical, and chemical properties. As a result, they are a good candidate for photochemistry, optoelectronics, photochemistry, and biological applications. The metal nanoparticles (Au, Cu, Ag, Pt, etc.) have unique physio-chemical properties which cannot be observed in individual molecules or bulk metals .…”
Section: Introductionmentioning
confidence: 99%
“…S12, ESI †), which does not apply to the exponential growth model but can be well fitted using the origin BiDoseResp function. 52,53 When the depression voltage is 1.4 V, the conductance gap of the first group is more negative than the aforementioned 0.9 V. With a larger depression amplitude, it takes more pulse groups before the potentiation pulse current reaches I cc , indicating that 1.4 V has a better inhibition effect than 0.9 V. However, the peak conductance of 1.4 V is higher than that of 0.9 V. Therefore, judging depression efficiency by comparing the conductance at the peak would be misleading. The higher peak conductance during the depression pulse may be attributed to the additional oxygen vacancies generated at the anode interface.…”
Section: Pulse Conductance Modulation and Relaxationmentioning
confidence: 99%